2019
DOI: 10.15649/2346075x.479
|View full text |Cite
|
Sign up to set email alerts
|

The seroprevalence of human brucellosis in different age groups patients and other associated risk factors in Duhok, Iraq

Abstract: Introduction: Brucellosis is a zoonotic disease contributing to significant health and economic problems worldwide. The aim of this study was to investigate the seroprevalence and the associated risk factors of brucellosis among people admitted to Azadi general hospital, Duhok, Iraq. Patients and Methods: A total of 1283 patient blood samples (603 males and 680 females) were collected through the period of January 2017 to December 2017 from people at different age groups admitting Azadi general hospital, Duhok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…A study conducted in the same hospital (Rizgari Hospital at Erbil) in 2012 reported a 10.7% prevalence which is close to the present study [22]. A slightly higher prevalence was found in another study conducted in Azadi general hospital in Duhok-Kurdistan, Iraq in 2017 with a seroprevalence rate of 17.8% [23]. Both studies were carried out among suspected patients of brucellosis using the RBT test.…”
Section: Discussionsupporting
confidence: 85%
“…A study conducted in the same hospital (Rizgari Hospital at Erbil) in 2012 reported a 10.7% prevalence which is close to the present study [22]. A slightly higher prevalence was found in another study conducted in Azadi general hospital in Duhok-Kurdistan, Iraq in 2017 with a seroprevalence rate of 17.8% [23]. Both studies were carried out among suspected patients of brucellosis using the RBT test.…”
Section: Discussionsupporting
confidence: 85%
“…This study found that 12.6% of patients in Duhok City/Iraq were positive for probable brucellosis, while another study also in Duhok city, in 2017 reported a higher seroprevalence rate of 17.8%. 18 On the other hand, a lower seroprevalence 2808 rate (10.7%) during 2012 was reported in Erbil city, Iraq. 19 In both of these studies, the analyzed data for RBT were from RBT people suspected to have brucellosis.…”
Section: Discussionmentioning
confidence: 93%
“…Childhood brucellosis infection was considered rare in the past, but more recent studies have shown that it is common among children in areas where brucellosis is endemic 25 . People aged 21-40 years were more infected in Saudi Arabia 26 , Kenya 21 , Iraq 27 , and Uganda 28 .…”
Section: Discussionmentioning
confidence: 99%